Impact of Polymer Side Chain Modification on OPV Morphology and Performance - Neophytou, Marios; Liu, Shengjian; Gu, Xiaodan; Savikhin, Victoria; Babics, Maxime; Beaujuge, Pierre M.; Oosterhout, Stefan D.; Yan, Hongping; Toney, Michael F. (My University, 2018)
Efficiencies of organic photovoltaic (OPV) devices have been steadily climbing, but there is still a prominent gap in understanding the relationship between fabrication and performance. Side chain substitution is one processing parameter that can change OPV device efficiency considerably, primarily because of variations in morphology. In this work, we explain the morphological link between side chain selection and device performance in one polymer to aid in the development of design rules more broadly. We study the morphology of an OPV active layer using a PBDTTPD-backbone polymer with four different side chain configurations, which are shown to change device efficiency by up to 4 times. The optimal device has the smallest domain sizes, the highest degree of crystallinity, and the most face-on character. This is achieved with two branched 2-ethylhexyl (2EH) side chains placed symmetrically on the BDT unit and a linear octyl (C8) side chain on the TPD unit. Substituting either side chain (C14 on BDT and/or 2EH on TPD) makes the orientation less face-on, while the TPD side chain primarily affects domain size. For all side chains, the addition of fullerene increases polymer crystallization compared to the neat film, but the degree of mixing between polymer and fullerene varies with side chain. Interestingly, the optimal device has a negligible amount of mixed phase. The domain sizes present in the optimal system are remarkably unchanged with a changing fullerene ratio between 10 and 90%, hinting that the polymer preferentially self-assembles into 10-20 nm crystallites regardless of concentration. The formation of this crystallite may be the key factor inhibiting mixed phase.
Keywords: conformal deposition; large area; nickel oxide; p-i-n perovskite device configuration; perovskite solar cells; room-temperature processing; sputtering